2008
DOI: 10.1159/000151517
|View full text |Cite
|
Sign up to set email alerts
|

Minor Psychiatric Disorders and Syncope: The Role of Psychopathology in the Expression of Vasovagal Reflex

Abstract: Background: A high prevalence of minor psychiatric disorders (MPDs) has been reported in patients with vasovagal syncope (VVS). However, the relationship between the psychiatric substrate and syncope remains unclear. Methods: In order to test the hypothesis that MPDs may predispose to VVS, we assessed the prevalence of syncope, the response to head-up tilt test (HUTT) and the efficacy of psychiatric drug treatment in reducing syncopal episodes, in patients with recently diagnosed MPDs. The response to HUTT was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…It has also been reported that the psychiatric disorder prevalence was 80% in patients with syncope [15,30,32]. Recently, a prospective study found that 45% of adult patients with depression or anxiety disorders had a history of syncope episode [33]. Similarly, anxiety [34], depression [35] and somatization disorder [30] prevalence were reported in patients with positive tilt table test and recurrent syncope episodes.…”
Section: -Tse Was Correlated Significantly and Positively Withmentioning
confidence: 92%
“…It has also been reported that the psychiatric disorder prevalence was 80% in patients with syncope [15,30,32]. Recently, a prospective study found that 45% of adult patients with depression or anxiety disorders had a history of syncope episode [33]. Similarly, anxiety [34], depression [35] and somatization disorder [30] prevalence were reported in patients with positive tilt table test and recurrent syncope episodes.…”
Section: -Tse Was Correlated Significantly and Positively Withmentioning
confidence: 92%
“…Treatment of general psychological complaints has been found to affect syncope-recurrence as well [16].…”
Section: Main Findingsmentioning
confidence: 99%
“…Psychiatry, neurology and cardiology research groups have found psychiatric conditions are over-represented in patients with vasovagal syncope, particularly anxiety, depression and somatization disorders (Giada et al, 2005 ). In psychiatry, a survey of 67 patients (Leftheriotis et al, 2008 ) identified 58% as showing a vasovagal episode during head up tilt and 45% had a history of syncope. Interestingly, vasovagal syncope patients who do not respond to treatment are more anxious on rat and depressed (on rating scales) than normal vasovagal syncope treatment responders and also report more negative thoughts regarding threats to physical harm or death as well as higher levels of avoidance/protection coping and rumination (Gracie et al, 2006 ).…”
Section: Neurovisceral Phenotypesmentioning
confidence: 99%